Academic Resilience as a Determinant of Student Engagement: A Perspective of Educational Management in Universities - Wahyu Nur Isna Wulandari; Riza Noviana Khoirunnisa (Journal of Educational Management Research, 2026)
Changes in higher education learning systems and the increasing complexity of academic demands require students to demonstrate resilience and sustained engagement in the learning process. Insufficient student engagement may negatively affect learning quality, academic achievement, and institutional effectiveness. This study examines the influence of academic resilience on student engagement among undergraduate psychology students at Universitas Negeri Surabaya. Employing a quantitative correlational design, data were collected from 326 students selected from a population of 2,122 active students using the Raosoft sample size calculation. Data collection was conducted through an online survey utilizing the Academic Resilience Scale (ARS-30) and the University Student Engagement Inventory (USEI). The findings reveal that academic resilience has a strong and statistically significant effect on student engagement, as indicated by a coefficient of determination of 0.968 (p < 0.05), demonstrating that academic resilience substantially contributes to students’ behavioral, emotional, and cognitive engagement. These results highlight academic resilience as a critical internal resource in supporting effective learning participation. From an educational management perspective, the findings emphasize the importance of integrating resilience-building strategies into academic support systems, learning management practices, and student development programs to enhance engagement, improve learning outcomes, and support sustainable academic success in higher education institutions